Search 80,000+ tutors
Ask a question
0 0

consider the equations f(x)=-6x-1 and g(x)=4x^2. What is the solution for (f+g)(x)?

Tutors, please sign in to answer this question.

2 Answers

Just as Philip has said, to find the answer to (f+g)(x), one simply adds [f(x)] + [g(x)] -- in this case, [-6x-1]+[4x2] = -6x-1+4x2, and then rearrange so the terms are in order of decreasing exponents, 4x2-6x-1.
You might notice that when the problem says f+g, that's literally what we did -- we added f(x) and g(x). Similarly, (f-g)(x) would be found by subtracting f(x)-g(x), (fg)(x) would be f(x)g(x), (f/g)(x) would be f(x)/g(x)... Order is important, mind you, (f-g)(x) is different from (g-f)(x), but basically you just do what the operator tells you to do. :)
If you have any more questions, let me know!
f(x) = -6x - 1
g(x) = 4x2
(f+g)(x) = -6x - 1 + 4x2
There are no like terms to combine, but you should re-arrange the terms to put them in order of decreasing exponents:
(f+g)(x) = 4x2 - 6x -1